A METHOD OF FINDING THE SOLUTION OF SOME IMPORTANT DIFFERENTIAL EQUATIONS - Komilov, A; Umrzakova, I; Eshbekov, R (Innovative Development in Educational Activities, 2023)
It is known that the mathematical model of many processes in our life is represented by differential equations, and it is important to find the solutions of these differential equations in a simpler way. This article presents a method of solving some important differential equations by expanding the solution into a power series.